The development of a prototype computerized school library catalog for the Saint Joseph Institute of Technology, Butuan City - Cabebe, Iris A. (2008)
This study intended to search the background and current status of Saint Joseph Institute of Technology Library. The researcher's objective was to design a cheaper and user-friendly program for the automation of library systems using Visual FoxPro version 8 for school libraries (specifically SJIT) to utilize.